The ethyl acetate extract of Vernonia amygdalina leaf ameliorates gemcitabine effect against migration and invasion of PANC-1 cells via down-regulation the VEGF, COX2, and RAS/MEK pathways - Poppy Anjelisa Zaitun Hasibuan; Jane Melita Keliat; Muhammad Fauzan Lubis; Annisa Nasution (Elsevier, 2024)
Individuals diagnosed with cancer often turn to the use of herbal remedies with the intention of treating and ameliorating the condition, impeding the progression of metastasis, enhancing immune function, mitigating stress, and inducing relaxation. Recently, medicinal plants were combined with conventional chemotherapy to decrease the side effects and increase the effectiveness of chemotherapy. This study showed the effectiveness of gemcitabine (Gem) was significantly increased after being used together with ethyl acetate extract obtained from Vernonia amygdalina (Eav) leaves. The combination doses of Eav and Gem were determined based on cytotoxic activity using the MTT assay method. The anticancer effect of this combination was identified by several parameters including the apoptosis effect, anti-migration, and anti-invasion activities of PANC-1 cells. Furthermore, this effect was explained via protein expression evaluation using immunohistochemical and flow cytometry. The Eav has a better Inhibitory Concentration 50 (IC50) than Gem of 21.19 ± 0.64 µg/mL and 164.78 ± 1.40 µg/mL. The combination of Eav and Gem at IC50 (1:1) has the strongest activity than Eav and Gem alone at 500.00 µg/mL. The anti-cancer effect of this combination showed significantly increased levels of apoptosis, particularly in the early phase of 17.46 ± 0.35 % (p < 0.0001) than Eav and Gem alone of 7.76 ± 0.25 % and 7.06 ± 0.20 %. A similar impact was evaluated in the migration and invasion of PANC-1 cells after the combination treatment. The % relative migration and cell invasion were significantly decreased compared to the control group and Eav or Gem alone by 21.49 ± 0.96 % and 125.25 ± 5.25 cells, respectively (p < 0.0001). This study found that signature molecules of VEGF, COX2, RAS, and MEK were down-regulated after treatment. Our study suggested that the Eav ameliorates the Gem effect against PANC-1 cells through apoptosis, migration, and invasion influence via RAS/MEK pathways.